A Champion for the Unestablished - Rarrick, Mohini P. B. (The Hastings Center report, 2019)
As a student in bioethics, I knew that The Hastings Center and its founders were the height of excellence in this field, and therefore I found them both intimidating and intriguing. When I began working there, Dan Callahan was supportive of my endeavors to provide a venue for students and other young writers to express their views on bioethics. I started my own blog called Bioethx under 25 that featured short essays by anyone who wished to submit, generally individuals who had a genuine philosophical interest but were not yet at the level of pursuing a Ph.D. Dan's support of my project culminated in his sponsorship of the Daniel Callahan Young Writer's Prize, an essay contest run through the blog. This was one of the many ways he demonstrated that making theoretical contributions to bioethics should not be limited to a select few.